Abscesso renal em pediatria - desafios para o diagnóstico e manejo: relato de caso - Alexandre Neves da Rocha Santos; Maria Cristina Andrade; Eduardo Freitas Hatanaka (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To discuss the diagnostic difficulties of renal abscess in the pediatric age and warn pediatrics about the possible complications of urinary tract infections. CASE DESCRIPTION: A 16-year-old boy with autism spectre disorder and Duchenne muscular dystrophy presented at the emergency care unit with persistent fever despite the use of antibiotics to treat an urinary tract infection. Although there was leukocyturia, the urine culture was negative. Ultrassound of the urinary tract showed no significant findings. Computed tomography showed multiple renal abscesses in the right kidney. A puncture guided by ultrasound was performed. The culture of the liquid resulted in growth of ESBL Klebsiella pneumoniae. A 21 day course of intravenous antibiotic after the procedure resulted in complete resolution of signs and symptoms. COMMENTS: Renal abscess is a rare condition in the pediatric population. However, it must be considered in the differential diagnosis of prolonged fever and when there is a non-favorable evolution of urinary tract infection, mainly in recurrent episodes. The early diagnosis of this condition is essential for the adequate treatment and reduction of complications.